HISTORICAL LANDSCAPE OF AN ISLAND TOWN: TERNATE, NORTH MALUKU - Amin, Basri (History Department, Semarang State University and Historian Society of Indonesia, 2017)
Maluku is not only well known for the hundreds spreading islands, but also for its long historical records. It is usually to say that the formation of national consciousness of Indonesia actually began since colonialism period, which all started with the presence of Western occupation in Maluku. This article will discuss how the historical background of Maluku archipelago leave a socio-cultural impact that is still continues until today. The historical experience and socio-political dynamics of Ternate are the prominent case chosen in this article to describe that a small (island) town can stimulate such a large historical contestation.Â Maluku bukan hanya terkenal karena sebaran ratusan pulaunya, tapi juga karena dinamika sejarahnya yang panjang. Bahkan bisa dikatakan bahwa pembentukan kesadaran nasional Indonesia dimulai sejak periode kolonialisme, hal mana itu bermula dari kehadiran bangsa Barat di kepulauan Maluku. Artikel ini akan menjelaskan bagaimana latar sejarah kolonial Maluku yang panjang itu terbukti menyisahkan dampak sosial budaya yang masih terus berlangsung hingga saat ini. Pengalaman sejarah dan dinamika sosial politik masyarakat pulau Ternate adalah kasus yang dipilih dalam artikel ini untuk menunjukkan bahwa sebuah kota pulau kecil bisa menampung (pertarungan) sejarah yang demikian besar.Â Â